Middle-class moralities : everyday struggle over belonging and prestige in India - Saavala, Minna (New Delhi : Orient Blackswan, 2010)
Study conducted in Hyderabad, Andhra Pradesh, India.
Includes index.
Bibliography : p. 210-222.
Keywords: Middle class -- India -- Hyderabad -- Conduct of life; Hindus -- India -- Hyderabad -- Conduct of life; Hyderabad (India) -- Social life and customs